Different LED light intensity and quality change perennial ryegrass (Lolium perenne L.) physiological and growth responses and water and energy consumption - Brito, Cátia; Ferreira, Helena; Dinis, Lia-Tânia; Trindade, Henrique; Marques, David; Correia, Carlos Manuel; Moutinho-Pereira, José (Frontiers in Plant Science, 2023)
Light intensity and spectral composition highly affect plant physiology, growth, and development. According to growing conditions, each species and/or cultivar has an optimum light intensity to drive photosynthesis, and different light spectra trigger photosynthetic responses and regulate plant development differently. For the maintenance of natural sports pitches, namely professional football competitions, turf quality is a key condition. Due to the architecture of most football stadiums, the lawns receive low intensities of natural light, so supplementary artificial lighting above the turf is required. The use of light-emitting diodes (LEDs) can have a higher cost–benefit ratio than traditional high-pressure sodium lamps. The continuous emission spectrum, combined with high spectral selectivity and adjustable optical power, can be used to optimize plant growth and development. Thus, perennial ryegrass (Lolium perenne L.) plants, commonly used for lawns, were primarily grown at three different intensities (200, 300, and 400 μmol m−2 s−1) of cool white light. Despite the higher water and energy consumption, 400 μmol m−2 s−1 maximizes the plant’s efficiency, with higher photosynthetic rates and foliar pigment concentration, and more foliar soluble sugars and aboveground biomass accumulation. Then, it was evaluated the perennial ryegrass (Double and Capri cultivars) response to different spectral compositions [100% cool white (W), 80% Red:20% Blue (R80:B20), 90% Red:10% Blue (R90:B10), and 65% Red:15% Green:20% Blue (R65:G15:B20)] at 400 μmol m−2 s−1. Both cultivars exhibited similar responses to light treatments. In general, W contributed to the better photosynthetic performance and R90:B10 to the worst one. Water consumption and aboveground biomass were equal in all light treatments. R80:B20 allows energy savings of 24.3% in relation to the W treatment, showing a good compromise between physiological performance and energy consumption.